SAVING THE WORLD IN DNA: RECENT PROGRESS IN DNA STORAGE TECHNOLOGY IN 2026 - Sonia Abakar; Brahim Gaba; Mahamat Saleh (Yayasan Adra Karima Hubbi, 2025)
The exponential expansion of the global datasphere is rapidly outpacing the physical and environmental capacity of silicon-based storage media. This study investigates the efficacy of a novel “dynamic-corrective” enzymatic synthesis architecture to address the critical cost and latency bottlenecks hindering the commercial adoption of DNA data storage. Utilizing a quantitative “bits-to-molecules-to-bits” experimental framework, we benchmarked an engineered Terminal Deoxynucleotidyl Transferase (TdT) protocol against traditional phosphoramidite chemistry, encoding a 10-terabyte heterogeneous dataset protected by hybrid LDPC-fountain codes. Empirical results demonstrate that the enzymatic system achieved a sustained write latency of 250 milliseconds per nucleotide and a synthesis cost of 0.05 per megabyte, representing a 70,000-fold reduction over chemical baselines. The system maintained a high logical density of 3.6 bits per nucleotide with 100% data recovery, while silica encapsulation proved stability equivalent to 500 years of aging. We definitively conclude that 2026-era enzymatic synthesis has matured into a scalable industrial solution, validating DNA as a robust, zero-energy archival medium essential for decarbonizing the future of global information infrastructure.